Navigating Comics II: Constraints on the Reading Order of Comic Page Layouts. Issue 2 (15th October 2014) - Cohn, Neil; Campbell, Hannah
Summary: Although readers typically believe that comic page layouts should be read following the left to right and down 'Z‐path' inherited from written language, several spatial arrangements can push readers to deviate from this order. These manipulations include separating panels from each other, overlapping one panel onto another, and using a long vertical panel to the right of a vertical column to 'block' a horizontal row. We asked participants to order empty panels in comic page layouts that manipulated these factors. All manipulations caused participants to deviate from the conventional Z‐path, and this departure was modulated by incremental changes to spatial arrangements: The more layouts deviated from a grid, the less likely participants were to use the Z‐path. Overall, these results reinforce that various constraints push comic readers to engage with panels in predictable ways, even when deviating from the traditional Z‐path of written language. Copyright © 2014 John Wiley & Sons, Ltd.